2014
DOI: 10.1186/1749-7922-9-38
|View full text |Cite
|
Sign up to set email alerts
|

Lemierre’s disease: a case with bilateral iliopsoas abscesses and a literature review

Abstract: Lemierre’s disease is characterized by sepsis, often with an oropharyngeal source, secondary septic emboli and internal jugular vein thrombosis (Lancet 1:701–3, 1936. Clin Microbiol Rev 20(4):622–59, 2007). Septic emboli affecting many bodily sites have been reported, including the lungs, joints, bones, and brain. The case report describes an unusual case of Lemierre’s disease in a 64 year old gentleman causing profound sepsis, acute kidney injury, bilateral iliopsoas abscesses and a right hand abscess. To our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…can be recovered from dental [33] parapharyngeal, retropharyngeal, [42,85] peritonsillar, [41] intracranial, [79,81] visceral, hepatic, [86] splenic, [86] subphrenic, [87] perirectal, [88] pilonidal, [89] pelvic, illeopsoas [90], and vulvovaginal abscesses [27]. Fusobacterial abscesses in the soft tissue of the limbs, breasts, lungs, and parotid gland have been reported.…”
Section: Abscessesmentioning
confidence: 95%
“…can be recovered from dental [33] parapharyngeal, retropharyngeal, [42,85] peritonsillar, [41] intracranial, [79,81] visceral, hepatic, [86] splenic, [86] subphrenic, [87] perirectal, [88] pilonidal, [89] pelvic, illeopsoas [90], and vulvovaginal abscesses [27]. Fusobacterial abscesses in the soft tissue of the limbs, breasts, lungs, and parotid gland have been reported.…”
Section: Abscessesmentioning
confidence: 95%
“…Iliopsoas abscess is a relatively rare disorder that has a diversity of frequency depending on patients' race, gender, and preexisting diseases [1]. Sequential iliopsoas abscess has been reported in the immunological suppression in rheumatoid arthritis, cervical spondylosis infection, ulcerative colitis, malignant tumor cases, and cardiovascular disorders [22][23][24][25][26]. Our study demonstrated that undernutrition is an indicator for the possible presence of IPA; however, serum inflammatory markers may not be useful to differentiate IPA from other inflammatory responses.…”
Section: Discussionmentioning
confidence: 68%
“… 2 In addition, metastasis of soft tissues has been reported, including bilateral psoas abscesses. 5 In our case, the pulmonary embolism and gluteal muscle abscesses could be considered as metastasis from IJV thrombosis.…”
Section: Discussionmentioning
confidence: 68%
“…2 In addition, metastasis of soft tissues has been reported, including bilateral psoas abscesses. 5 In our case, the pulmonary embolism and gluteal muscle abscesses could be considered as metastasis from IJV thrombosis. Empirical treatment for jugular vein suppurative thrombophlebitis should include a beta-lactam with a beta-lactamase inhibitor and an antibiotic with good anaerobic coverage.…”
Section: Discussionmentioning
confidence: 68%